The Influence of Leadership and its Dimensions on The Organizational Loyalty of Faculty Members in Saudi Universities: The Ideal Effect, Caring for Individuals, Mental Stimulation, Inspirational Catalysis - Al Shehry, Waleed (The Arab Journal of Administration, 2023)
Functional performance in any organization is the key to its success regardless of the nature of its activity. To achieve this, it is necessary to achieve functional loyalty that has a great role to obtain the highest levels of performance. Modern societies witnessing a remarkable interest in the importance of education, its role in the renaissance and prosperity of nations, The governments has given utmost importance to the issue of education in all its stages, especially at the university level, As a result, huge budgets have been allocated to the renaissance of university education and its role in providing society with an educated human resource equipped with modern sciences for the development of society. Universities are among the most important institutions for creating knowledge and advancing societies. Universities also play an active and important role in the development process as a scientific and academic organizational structure that brings about more processes of social and economic change in society, by supplying its various sectors with qualified, and trained with the latest knowledge, and this depends on the efficiency and effectiveness of the faculty member. Therefore, this study focused on functional loyalty and its relationship to transformational leadership represented in its dimensions (ideal effect, caring for individuals, mental stimulation, Inspirational catalysis), which have a role in achieving functional loyalty, which in turn raises the performance of faculty members in Saudi universities to the international standards.